Implementation of Khitobah Arabiyah for the Mastery of the Maharah Kalam of Class II Students of Kuliyatul Mu'alimin Al-Islamiyah at the An-Nida Islamic Boarding School Selomerto - Amalia, Lia; Rizqi, Soffan; Faturrokhman, Faturrokhman (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
This study aims to: 1) Find out how the implementation of the Khitobah Arabiyah for the mastery of the maharah kalam of class II Kuliyatul Mu'alimin Al-Islamiyah students at the An-Nida Islamic Boarding School Wonosobo; 2) Find out the supporting and inhibiting factors of the Khitobah Arabiyah for class two Kuliyatul Mu'allimin Al-Islamiyah students at the An-Nida Islamic Boarding School Selomerto Wonosobo; 3) To find out the results of the mastery of the maharah kalam of students with the presence of the khitobah Arabiyah. This study uses a qualitative approach where the type of research is field research. Data collection techniques use observation, interview, and documentation methods related to the implementation of the khitobah Arabiyah. The analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the study show that; 1) The implementation of the Khitobah Arabiyah significantly helps in the mastery of the maharah kalam of students. The Khitobah Arabiyah is carried out routinely every Saturday night, and once a month a grand sermon is held. The first step is determining the theme of the language section, compiling the text by the students, submitting the sermon text in the language section, guidance and revision of the language section. Then the implementation, with a series of sermons including a host who guides the implementation of the khitobah Arabiyah, reading the holy verses of the Qur'an, and the core, namely the khitobah Arabiyah, and finally direct evaluation; 2) Supporting factors for the implementation of the Khitobah Arabiyah include encouragement and motivation from the caretaker and administrators, facilities and infrastructure, motivation of the students' enthusiasm, preparation of materials. While inhibiting factors include the lack of self-confidence of the students, the students' language skills, lack of intensive mentoring. The solution to overcome these obstacles is with a personal approach, more intensive guidance, involving senior students who are experienced and have better Arabic language skills; 3) The results of students' mastery of maharah kalam with the presence of Khitobah Arabiyah are an increase in fluency in active speaking, especially for students who were previously passive or preferred to remain silent because they found it difficult to speak Arabic, understanding of language structure (grammatical), through the compilation of Khitobah Arabiyah texts, students begin to understand the sentence structure in Arabic, although there are still a few grammatical errors, vocabulary mastery, because Khitobah Arabiyah enrich students' vocabulary, students' confidence in speaking increases significantly, especially for shy students, because they are used to speaking Arabic in front of an audience, the application of Arabic is increasingly active, students not only learn theory but also apply Arabic in real practice.